Weight bias among health care professionals: A systematic review and meta‐analysis. Issue 11 (6th September 2021) - Lawrence, Blake J.; Kerr, Deborah; Pollard, Christina M.; Theophilus, Mary; Alexander, Elise; Haywood, Darren; O'Connor, Moira
Abstract: Objective: Weight‐biased attitudes and views held by health care professionals can have a negative impact on the patient‐provider relationship and the provision of care, but studies have found mixed results about the extent and nature of bias, which warrants a review of the evidence. Methods: A systematic review and random‐effects meta‐analysis were conducted by including studies up to January 12, 2021. Results: A total of 41 studies met inclusion criteria, with 17 studies providing sufficient data to be meta‐analyzed. A moderate pooled effect (standardized mean difference = 0.66; 95% CI: 0.37‐0.96) showed that health care professionals demonstrate implicit weight bias. Health care professionals also report explicit weight bias on the Fat Phobia Scale, Antifat Attitudes Scale, and Attitudes Towards Obese Persons Scale. Findings show that medical doctors, nurses, dietitians, psychologists, physiotherapists, occupational therapists, speech pathologists, podiatrists, and exercise physiologists hold implicit and/or explicit weight‐biased attitudes toward people with obesity. A total of 27 different outcomes were used to measure weight bias, and the overall quality of evidence was rated as very low. Conclusions: Future research needs to adopt more robust research methods to improve the assessment of weight bias and to inform future interventions to address weight bias among health care professionals.